Interferensi Fonologis Penggunaan Bahasa Sunda pada Penutur Sunda Kelahiran Banten di Karawang - Masitoh, Siti; Nurfadilah, Kurnia Dewi (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2025)
This study aims to describe and identify several differences in language use by Sundanese Karawang speakers born in Banten (PS-KKB). In this study, a qualitative method with a case study approach at PS-KKB in Karawang was carried out using participatory observation techniques and interviews with 30 informants which were carried out naturally through ethnographic techniques. The analysis was carried out using the determinant element separation technique and 4 additional phonemes were found in the form of paragogue, epenthesis and prothesis such as [ña] becomes [ñah], [ka] becomes [kana], [atɔs] becomes [əntɔs] and [əŋké] becomes [engkin], as well as 5 phoneme substitutions such as [waé] becomes [baé], [dUh] becomes [bUh], [néng] becomes [nong], [da] becomes [ja], [arék] becomes [adék]. There were also 10 word substitutions from [atUh] to [géh], [tərUs] to [lajU], [pisan] to [amat], [manéh] to [dĩa], [mit-amit] to [tĩŋ-batĩŋ], [siga] to [dowaŋ], [ayɤna] to [kĩwari], [uwa] to [əndé], [dɤh] to [aĩh], [nəmən] to [kabina-bina]. The factors causing the interference of Sundanese Banten dialect are mostly dominated by the lack of adaptation to the Sundanese Karawang dialect and the influence of bilingualism possessed by the speaker, while the rest is influenced by the lack of exploration of the speaker towards the use of the Sundanese Karawang dialect. The results of this study can contribute to the study of phonology related to interlanguage, especially in understanding the patterns of sound interference from the mother tongue into the second language.